Control of the growth of human breast cancer cells in culture by manipulation of arachidonate metabolism - Zhang XiaoYan; Sumaida Dena; Hammamieh Rasha; Das Rina; Jett Marti (BMC Cancer, 2007)
Abstract Background Arachidonate metabolites are important regulators of human breast cancer cells. Production of bioactive lipids are frequently initiated by the enzyme phospholipase A2 which releases arachidonic acid (AA) that is rapidly metabolized by cyclooxygenases (COX) or lipoxygenases (LO) to other highly potent lipids. Methods In this study we screened a number of inhibitors which blocked specific pathways of AA metabolism for their antiproliferative activity on MCF-7 wild type and MCF-7 ADR drug resistant breast cancer cells. The toxicity of these inhibitors was further tested on human bone marrow cell proliferation. Results Inhibitors of LO pathways (specifically the 5-LO pathway) were most effective in blocking proliferation. Inhibitors of platelet activating factor, a byproduct of arachidonate release, were also effective antiproliferative agents. Curcumin, an inhibitor of both COX and LO pathways of eicosanoid metabolism, was 12-fold more effective in blocking proliferation of the MCF-7 ADRs cells compared to MCF-7 wild type (WT) cells. These inhibitors that effectively blocked the proliferation of breast cancer cells showed varying degrees of toxicity to cultures of human bone marrow cells. We observed greater toxicity to bone marrow cells with inhibitors that interfere with the utilization of AA in contrast to those which block utilization of its downstream metabolites. MK-591, MK-886, PCA-4248, and AA-861 blocked proliferation of breast cancer cells but showed no toxicity to bone marrow cells. Conclusion These inhibitors were effective in blocking the proliferation of breast cancer cells and may be potentially useful in human breast cancer therapy.